Analisis Strategi Pengembangan Agroindustri Tahu Bulat di Dusun Buniasih Desa Muktisari Kecamatan Cipaku Kabupaten Ciamis : (Studi Kasus pada Agroindustri Tahu Bulat Putra Mandiri di Dusun Buniasih Desa Muktisari Kecamatan Cipaku Kabupaten Ciamis) - Agus Hendar; Yaya Sunarya; D Yadi Heryadi (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
The aim of this research is to analyze internal and external factors and determine strategy choices in developing the round tofu agroindustry. This research uses a qualitative approach with case study methods and SWOT matrix analysis. Internal Strength Factors (Strength): Putra Mandiri's tofu agroindustry has well-organized management, adequate processing machine capabilities, and maintained product quality. Weakness: Increasing employee capacity is still situational, and processing machines are not yet equipped with an automatic system. External Factors: Opportunities: There is demand for round tofu products from outside the island, soybeans are available as raw materials, and the majority of competitors are in Cipaku District, providing room for expansion. Threat: Round tofu products have limited durability, raw material prices tend to fluctuate, and price competition is tight. Based on the SWOT analysis, the strategy that can be implemented is the S-O (Strength-Opportunity) Strategy, namely by maximizing the quality of round tofu, meeting market demand, collaborating with other factories, and establishing partnerships with modern markets to expand product distribution.